PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGOLAHAN PANGAN DI DESA KEMBANGLIMUS KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Natalina Kristiani; Dwi Joko Siswanto (JURNAL MAHATVAVIRYA, 2022)
Empowerment is a process that requires thorough planning, careful thought about monitoring mechanisms, and continuous improvement. This journal aims to determine the economic conditions of the community, processing crops, and empowering them. The research location is in Kembanglimus village, Borobudur sub-district, Magelang district with the subjects of PKK mothers and young women. The results obtained are as follows: Descriptively, community economic empowerment through food processing in Kembanglimus is still not in accordance with the government's target (which is expected). Agricultural/ plantation crops are only sold cheaply, they cannot even improve the community's economy. The obstacles faced in empowering the community's economy through processed papaya fruit are the low level of education, low willingness, lack of human resources and limited capital. Efforts made by the government are to expand business opportunities to improve the community's economy by providing opportunities in the field of skills through training and motivating PKK mothers and young women in the village of Kembanglimus through crop processing training that can open entrepreneurship and increase selling value.